Toothpastes and enamel erosion/abrasion – Impact of active ingredients and the particulate fraction. (November 2016) - Ganss, C.; Marten, J.; Hara, A.T.; Schlueter, N.
Abstract: Objectives: To investigate in vitro a range of differently characterised toothpastes with respect to their efficacy in an erosion/abrasion setting with special emphasis on the role of the particulate ingredients. Methods: Human enamel samples were erosively demineralised with citric acid (2 min, 6×/day; 0.5%, pH 2.5; 10 days) and immersed in slurries (2 min, 2×/day) either without or with brushing (15 s, load 200 g). The toothpastes were eight NaF-toothpastes, three hydroxyapatite-toothpastes (one without and two with NaF), one fluoride-free chitosan-toothpaste and three Sn-toothpastes. Negative control was erosion only, positive control was SnF2 gel. Tissue loss was quantified profilometrically. Results: The SnF2 gel was most effective (reduction of tissue loss of 79%). Most of the products reduced tissue loss significantly when applied as slurries (between 28 and 66%). Brushing increased tissue loss in almost all toothpastes, only 5 formulations (all Sn-toothpastes and 2 NaF-toothpastes) reduced tissue loss significantly when compared to negative control (between 33 and 59%). There was a non-linear association between abrasiveness and amount of particles in a formulation, the particle size had no impact. Conclusions: Toothpastes had a protecting effect when applied as slurries but to a much lesser degree when applied with brushing. The particulate fraction may be a determinant for toothpaste efficacy in erosion/abrasion settings. Clinical significance: Toothpastes are important carriers of active agents against erosion, but physical impacts through brushing modifies efficacy distinctly. Understanding the role of the particulate fraction in toothpastes may offer perspectives for designing effective formulations for patients with erosive lesions.